The Effects of Prioritizing Lead or Boulder Climbing Among Intermediate Climbers - Stien, Nicolay; Frøysaker, Tor Frithjof; Hermans, Espen; Vereide, Vegard Albert; Andersen, Vidar; Saeterbakken, Atle Hole (Frontiers in Sports and Active Living, 2021)
This study compared the effects of prioritizing lead climbing or boulder climbing on climbing-specific strength and endurance, as well as climbing performance. Fourteen active climbers were randomized to a boulder climbing training group (BCT: age=27.2±4.4 years, body mass=65.8±5.5kg, height=173.3±3.8cm) or a lead-climbing training group (LCT: age=27.7±6.1 years, body mass=70.2±4.4kg, height=177.7±4.4cm). The groups participated in a five-week training period consisting of 15 sessions, performing either two weekly bouldering sessions and one maintenance-session of lead-climbing (BCT) or two weekly lead-climbing sessions and one maintenance-session of bouldering (LCT). Pre- and post-training, maximal force and rate of force development (RFD) were measured during isometric pull-ups performed on a jug hold and a shallow rung, and during an isolated finger-strength test. Lead-climbing and bouldering performance were also measured, along with an intermittent forearm endurance test. The pre-to-post changes were not significantly different between the groups for any of the parameters (P=0.062–0.710). However, both the BCT (ES=0.30, P=0.049) and LCT (ES=0.41, P=0.046) groups improved strength in the isometric pull-up performed using the jug, whereas neither group improved force in the rung condition (P=0.054 and P=0.084) or RFD (P=0.060 and P=0.070). Furthermore, climbing and bouldering performance remained unchanged in both groups (P=0.210–0.895). The LCT group improved forearm endurance (ES=0.55, P=0.007), while the BCT group improved isolated finger strength (ES=0.35, P=0.015). In addition to isometric pull-up strength, bouldering can increase isolated finger strength while lead-climbing may improve forearm endurance. A five-week period prioritizing one discipline can be safely implemented for advanced to intermediate climbers without risking declined performance in the non-prioritized discipline.